2015
DOI: 10.1371/journal.pone.0142176
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Indigestible Carbohydrates, Protein Type, and Protein Level on Biomarkers of Large Intestine Health in Rats

Abstract: The effects of indigestible carbohydrates, protein type, and protein level on large intestine health were examined in rats. For 21 days, 12 groups of six 12-week-old male Wistar rats were fed diets with casein (CAS), or potato protein concentrate (PPC), providing 14% (lower protein level; LP), or 20% (higher protein level; HP) protein, and containing cellulose, resistant potato starch, or pectin. Fermentation end-products, pH, and β-glucuronidase levels in cecal digesta, and ammonia levels in colonic digesta w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
2
15
0
1
Order By: Relevance
“…2). These findings are consistent with a previous report in which the consumption of indigestible carbohydrates induced fermentation in the cecum (24), which has been shown to positively affect microbial composition and immune responses in the large intestine of rats (17). The upregulation of IgA secretion in the cecum is caused by various antigens, such as bacterial cell wall constituents or decomposed and fermented products of indigestible carbohydrates, generated as a result of increased fermentation by intestinal microflora (25).…”
Section: Discussionsupporting
confidence: 92%
“…2). These findings are consistent with a previous report in which the consumption of indigestible carbohydrates induced fermentation in the cecum (24), which has been shown to positively affect microbial composition and immune responses in the large intestine of rats (17). The upregulation of IgA secretion in the cecum is caused by various antigens, such as bacterial cell wall constituents or decomposed and fermented products of indigestible carbohydrates, generated as a result of increased fermentation by intestinal microflora (25).…”
Section: Discussionsupporting
confidence: 92%
“…It was also revealed that supplementing rats with PEC, and to a lesser extent POM, increased the small intestinal mass. Other researchers have also shown a similar effect of pectin (Pirman et al, 2007;Taciak et al, 2015), which may result from accumulation of a high-moisture and viscous digesta and from its prolonged passage through the proximal part of the digestive tract. Pectin increased also maltase activity in the small intestine, which might be an adaptive response to greater digesta weight and viscosity but also to morphological changes as it was indicated by Schwarz et al (1983) and Koruda et al (1988).…”
Section: Discussionmentioning
confidence: 72%
“…Despite this, adding resistant starch to these high protein diets nullified the negative effects of high protein consumption [135], further illustrating the importance of consuming adequate dietary fiber for gut and overall health. Another study examined the effects of protein type, and protein level on large intestine health in rats [136]. Lower levels of cecal BCAA were found in rats who ate a lower protein diet (14% of total energy) than those who consumed a high protein diet (20% of total energy) [136].…”
Section: Main Textmentioning
confidence: 99%
“…Another study examined the effects of protein type, and protein level on large intestine health in rats [136]. Lower levels of cecal BCAA were found in rats who ate a lower protein diet (14% of total energy) than those who consumed a high protein diet (20% of total energy) [136]. These authors also showed that plant-based protein proved to be beneficial compared to animal protein, where potato protein concentrate (PPC) consumption positively impacted colonic health by reducing enzymatic activity of β-glucuronidase, which is a biomarker for the risk of carcinogenesis [136].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation